Contextualizing Quality in Education: Stakeholder Perspectives from Ghana’s Colleges of Education - Akosah, Ernest Frimpong; Bonney, Ebenezer Appah (Journal of Innovation in Academia, 2025)
This study explored quality assurance practices in Ghanaian Colleges of Education, highlighting challenges and proposing solutions to improve teaching and learning. Using a phenomenological approach, data were collected from 15 participants across five Colleges of Education, including principals, quality assurance officers, and student leaders. Findings revealed that internal quality mechanisms, academic counseling, and staff workshops enhance teaching quality. However, issues such as delayed result releases, curriculum irrelevance, and outdated resources persist. Participants recommended updating curricula, improving infrastructure, and strengthening professional development. The study provides context-specific insights into educational quality enhancement in resource-limited settings.